Twitter analysis of founders of top 25 Indian startups. (24th May 2019) - Sindhani, Mohit; Parameswar, Nakul; Dhir, Sanjay; Ongsakul, Viput
With the recent growth in social media dominance over the internet, many people have turned to these media to share their personal views, express their opinions and interact socially. This paper examines the social media content of Indian Chief Executive Officers who are the founders or co-founders of the top 25 Indian startups. The active involvement of Chief Executive Officers in social media influences the business effectiveness, performance and market legitimacy of the business. Social media has now become a crucial strategic tool from creating a buzz among businesses to engaging public in a new direction of thoughts. The paper has taken into consideration about 165, 987 tweets from the top startups and their cofounders. The tools used for tweets extraction and analysis are Anaconda Navigator and TIBCO Spotfire. The tweets seem to cover various aspects of emotions ranging from business sector to personal feelings, political views and societal concerns.